2020
DOI: 10.1038/s41467-020-18398-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of mercury released from thawing permafrost

Abstract: Mercury (Hg) is a naturally occurring element that bonds with organic matter and, when converted to methylmercury, is a potent neurotoxicant. Here we estimate potential future releases of Hg from thawing permafrost for low and high greenhouse gas emissions scenarios using a mechanistic model. By 2200, the high emissions scenario shows annual permafrost Hg emissions to the atmosphere comparable to current global anthropogenic emissions. By 2100, simulated Hg concentrations in the Yukon River increase by 14% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 34 publications
(73 reference statements)
0
67
0
Order By: Relevance
“…As riverine output intensifies, these waters carry higher concentrations of elements towards the coastal environment. (Perryman et al 2020;Polyakov et al 2010;Tovar-Sánchez et al 2010;Schaefer et al 2020). Rember and Trefry (2004) found that trace metal (Fe, Cu, Pb, Zn) concentrations in Alaskan rivers were highest during deluges from snowmelt and erosion of upper soil layers.…”
Section: Resultsmentioning
confidence: 99%
“…As riverine output intensifies, these waters carry higher concentrations of elements towards the coastal environment. (Perryman et al 2020;Polyakov et al 2010;Tovar-Sánchez et al 2010;Schaefer et al 2020). Rember and Trefry (2004) found that trace metal (Fe, Cu, Pb, Zn) concentrations in Alaskan rivers were highest during deluges from snowmelt and erosion of upper soil layers.…”
Section: Resultsmentioning
confidence: 99%
“…This is because population distribution in the Arctic does not always correspond with fixed asset allocations, such as buildings and structures. The authors compiled a database on more than thirteen thousand enterprises operating in the Arctic regions and estimated the market value of buildings and structures based on the average share values of those Permafrost regions are known for having large quantities of materials that may have health implications, such as mercury, as well as byproducts of mining, petroleum development, and solid waste (Grebenets et al 2021a;Schaefer et al 2020). Puchkov et al (2021 present a compelling review focused on yet another potential hazard associated with permafrost degradation -release of radon that may have detrimental impacts on the health and wellbeing of communities and industrial centers on permafrost.…”
Section: Permafrost Impacts On Economy and Healthmentioning
confidence: 99%
“…The area of near-surface permafrost in the Northern Hemisphere is projected to decline by 20% relative to today's area by 2040 and could be reduced by as much as two-thirds by 2080 under a scenario of high greenhouse gas emissions [26]. Impacts will vary widely at regional and local scales, but local effects are difficult to project given the lack of fine-scale detail in models and will involve a range of other environmental risks such as mercury contamination [27][28][29].…”
Section: Permafrostmentioning
confidence: 99%